Activation Strategies of Perovskite‐Type Structure for Applications in Oxygen‐Related Electrocatalysts. Issue 6 (17th April 2021) - Wei, Yicheng; Weng, Zheng; Guo, Linchuan; An, Li; Yin, Jie; Sun, Shuoyi; Da, Pengfei; Wang, Rui; Xi, Pinxian; Yan, Chun‐Hua
Abstract: The oxygen‐related electrochemical process, including the oxygen evolution reaction and oxygen reduction reaction, is usually a kinetically sluggish reaction and thus dominates the whole efficiency of energy storage and conversion devices. Owing to the dominant role of the oxygen‐related electrochemical process in the development of electrochemical energy, an abundance of oxygen‐related electrocatalysts is discovered. Among them, perovskite‐type materials with flexible crystal and electronic structures have been researched for a long time. However, most perovskite materials still show low intrinsic activity, which highlights the importance of activation strategies for perovskite‐type structures to improve their intrinsic activity. In this review, the recent progress of the activation strategies for perovskite‐type structures is summarized and their related applications in oxygen‐related electrocatalysis reactions, including electrochemistry water splitting, metal–air batteries, and solid oxide fuel cells are discussed. Furthermore, the existing challenges and the future perspectives for the designing of ideal perovskite‐type structure catalysts are proposed and discussed. Abstract : Improving the efficiency of energy storage and conversion devices requires the development of highly efficient and stable oxygen‐related catalysts. This review focuses on the basic understanding of oxygen‐related reactions. Meanwhile, the recent advances of perovskite‐type oxides for catalyzing several key reactions, recent progress in mechanisms, the activation strategies for boosting activity and stability, and the up‐to‐date electrocatalysts are discussed.